Alprostadil vs. isosorbide dinitrate in ameliorating angina episodes in patients with coronary slow flow phenomenon: A randomized controlled trial - Zhang, Weifeng; Dai, Jinjie; Shen, Lan; Jiang, Yue; Zheng, Xiaowen; Xu, Ke; Yang, Xiaoxiao; Wang, Xiaolei; Hao, Ziyong; Zhao, Yu; Wang, Dong; Jiang, Lisheng; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background The optimum therapy for coronary slow flow phenomenon (CSFP) stays debatable. This study compared the effectiveness of alprostadil with isosorbide dinitrate in alleviating angina episodes in CSFP patients. Methods In this prospective, randomized controlled study, 102 patients with CSFP without severe coronary artery stenosis that exhibited stable angina were allocated randomly in a ratio of 1:1 to either the alprostadil group (40 μg, three times per day, n = 51) or the isosorbide dinitrate group (5 mg, three times per day, n = 51). Frequency of angina events, intensity of suffering, and the Canadian Cardiovascular Society (CCS) grading of angina pectoris were evaluated at baseline and one month after. Additionally, the Seattle Angina Questionnaire (SAQ) was assessed. Results Baseline characteristics were comparable between the two groups. At 1-month follow-up, patients administered with alprostadil experienced fewer angina episodes [episodes per week, 1 (2) vs. 2 (2), P < 0.001] and less pain intensity [self-evaluated pain score, 2 (3) vs. 3 (4), P < 0.001] than those with isosorbide dinitrate. In the alprostadil group, 78.4% of patients were classified as CCS class I, significantly higher than the 47.1% seen in the isosorbide dinitrate group (P = 0.001). Furthermore, treatment of alprostadil led to a significant improvement in the SAQ score (7.09 U, 95% CI: 4.22–9.96, P < 0.001) compared to isosorbide dinitrate. Additionally, fewer patients suffered headaches when receiving alprostadil (7.8% vs. 19.6%, P = 0.084). Conclusion Alprostadil was more effective in ameliorating angina symptoms in CSFP patients than isosorbide dinitrate. Clinical trial registration [www.chictr.org.cn], identifier [ChiCTR2000033233].